Domestic investors and stock market involvement before and after the 2021 stock market disruption and investment uncertainty in Lagos State, Nigeria (Nigerian Journal of Cooperative Economics and Management, 2026)
The 2021 stock market disruption and investment uncertainty in Nigeria has continued to influence domestic investment profile. Previous studies on stock market have focused largely on portfolio diversification, with little attention paid to domestic investors’ level of involvement before and after the disruption. The study was anchored on Rationalisation Theory, while descriptive qualitative design was employed. Purposive and snowball sampling techniques were utilized to select 40 investors, 3 stockbrokers and 6 regulatory agencies (3 NGX AND 3 SEC staff) based on their professional capabilities. Data were thematically analysed. The findings revealed that domestic investors responded to perceived market uncertainty by re-allocating capital from equities to alternative investments channels offering higher expected returns and lower perceived risks, reflecting a rational assessment of changing market condition as stipulated in Rationalisation Theory assumptions. The study also discovered that domestic investors were actively involved in stock market activities before the 2021 stock market disruption due to high returns on investment (ROI), whereas there was a sharp decline in the level of their involvement in post 2021 stock market disruption era, despite regulators’ concerted efforts to stabilize the market. The study concludes that domestic investors’ stock market involvement is best explained as a rational decision making process of minimizing losses. It recommends promotion of financial literacy, re-inforcement of regulatory frameworks and long-term investment culture in the bid to guarantee stock market growth and sustainability in Nigeria.
Keywords: Domestic investors; involvement; Lagos; stock market stress